PENERAPAN PEMBELAJARAN MEDIA DIGITAL INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR DI SDN 014 SUMBERJO - Sahabuddin; Wahab, Abdul; Banna, Andi; Bunyamin, Andi; Mustamin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ learning outcomes in Islamic Religious Education and Character Building through the implementation of interactive digital media. The research method used is Classroom Action Research (CAR), which was conducted in two cycles: Cycle I and Cycle II. The subjects of this study were 31 sixth-grade students of SD Negeri 014 Sumberjo, Polewali Mandar Regency. Data collection techniques included observation, tests, and documentation. The results showed that the implementation of interactive digital media was able to improve students’ learning outcomes. In Cycle I, learning mastery had not yet reached the expected target because students were still adapting to the learning method. However, after improvements were made in Cycle II through the use of interactive media based on the Wordwall game, there was a significant increase, with 93.5% of students achieving the minimum mastery criteria. In addition, the use of interactive digital media also increased students’ activeness, motivation, and engagement in the learning process. Therefore, it can be concluded that interactive digital media is effective in improving learning outcomes in Islamic Religious Education and Character Building at the elementary school level.